УМІЛЕ ВИКОРИСТАННЯ РІЗНИХ ГРАФІЧНИХ МАТЕРІАЛІВ - НЕОБХІДНА УМОВА ДЛЯ ОВОЛОДІННЯ МИСТЕЦТВОМ НАЧЕРКУ (Педагогіка вищої та середньої школи, 2009)
Line and spot - a main graphic language dements and expressive facilities of the sketch and sketching. In article is considered question of the broad use the technical possibilities different graphic material for decision creative and scholastic problems. The Influence of the skill to use the different material in work with sketch and sketching on development of the figurative thinking, mental abilities, keenness of observation student.